Comparative studies of calcium antagonizing effect on acute toxicity of streptomycin and gentamicin in mice. - Abbas, Duraid A. (The Iraqi Journal of Veterinary Medicine, 2004)
Comparative studies about the characteristics of the acute toxicity of streptomycin and gentamicin and the antagonization effect of calcium to their toxicity were performed in mice. This was made by comparing the time of appearance and disappearance of toxicity symptoms of this aminoglycoside before and after calcium therapy and also by comparing the LD50 value of both agents. It was concluded that streptomycin is less potent but more efficacious as toxic agent than gentamicin and that calcium had a competitive inhibitory effect to the toxicity of aminoglycoside perhaps because of the similarity in their charges and binding sites. Calcium therapy seems to offer quantitatively the same protective level for both agents (nearly one time) but qualitatively better protective level against acute toxicity of streptomycin in mice than for gentamicin.